A Natural Antimicrobial Agent: Analysis of Antibacterial Effect and Mechanism of Compound Phenolic Acid on Escherichia coli Based on Tandem Mass Tag Proteomics - Zhang, Geyin; Yang, Yunqiao; Memon, Fareed Uddin; Hao, Kaiyuan; Xu, Baichang; Wang, Shuaiyang; Wang, Ying; Wu, Enyun; Chen, Xiaogang; Xiong, Wenguang; Si, Hongbin (Frontiers in Microbiology, 2021)
The objective of this study was to evaluate the antibacterial mechanisms of phenolic acids as natural approaches against multi-drug resistant Escherichia coli (E. coli). For that purpose, five phenolic acids were combined with each other and 31 combinations were obtained in total. To select the most potent and effective combination, all of the obtained combinations were examined for minimum inhibitory concentration (MIC) and it was found that the compound phenolic acid (CPA) 19 (protocatechuic acid, hydrocinnamic acid, and chlorogenic acid at concentrations of 0.833, 0.208, and 1.677 mg/mL, respectively) showed better efficacy against E. coli compared to other combinations. Furthermore, based on tandem mass tag (TMT) proteomics, the treatment of CPA 19 significantly downregulated the proteins associated with resistance (Tsr, Tar, CheA, and CheW), OmpF, and FliC of multidrug-resistant E. coli. At the same time, we proved that CPA 19 improves the sensitivity of E. coli to antibiotics (ceftriaxone sodium, amoxicillin, fosfomycin, sulfamonomethoxine, gatifloxacin, lincomycin, florfenicol, cefotaxime sodium, and rifampicin), causes the flagellum to fall off, breaks the structure of the cell wall and cell membrane, and leads to macromolecules leaks from the cell. This evidence elaborated the potential therapeutic efficacy of CPA 19 and provided a significant contribution to the discovery of antibacterial agents.